Unfortunate destiny: animals in the Indian Buddhist imagination - Ohnuma, Reiko (Oxford University Press, 2017)
This book constitutes the first major study of Indian Buddhist ideas about nonhuman animals and the roles played by animal characters in Buddhist literature